(untitled) (Medico Legal Update, 2019)
One of the government’s efforts in controlling hypertension, among others, is by launching the Germas (Healthy Living Movement) through activities: increasing physical activity, consumption of vegetables and fruits, regular health checks and not smoking. Through its tasks in the health sector, families are expected to be able to apply early to all family members about how to control hypertension through Germas. This study was to analyze the effect of knowledge, attitudes and actions on the implementation of family health tasks in controlling hypertension. This study used a cross sectional design conducted where subjects consisted of 120 family heads/family members. Data on knowledge, attitude, action, implementation of family health tasks in controlling hypertension through the Germas approach were obtained. Almost all subjects had good knowledge in the category, most of them had an attitude in the good category, most of them had an action in the sufficient category. This study shows a significant influence of knowledge, attitude and action on the implementation of family health tasks in controlling hypertension.